2017
DOI: 10.1017/s1368980017001665
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and facilitators of ultra-processed food consumption: perceptions of Brazilian adults

Abstract: Participants perceived their neighbourhoods as favourable to the consumption of ultra-processed foods and reported more facilitators than barriers to their consumption. Reported barriers point to the need to include measures promoting a healthy food system and traditional eating practices. The facilitators reinforce the idea that these foods are habit-forming and that regulatory measures to offset the exposure to ultra-processed foods are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
(48 reference statements)
0
27
0
10
Order By: Relevance
“…The influence of child preference on caregivers' use of snack food products for child feeding has been noted widely in literature across geographies (Almeida, Scagliusi, Duran, & Jaime, ; Angeles‐Agdeppa, Lana, & Barba, ; Babington & Patel, ; Feeley et al, ; Machín, Giménez, Curutchet, Martínez, and Ares (); Kavle et al, ; Pries, Huffman, Adhikary, et al, ; Pries, Huffman, Mengkheang, et al, ; Rahman et al, ; Verma & Punia, ; Vitta et al, ). Child preference was the most common reason reported by caregivers in this study; however, this response may serve as an initial catch‐all response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of child preference on caregivers' use of snack food products for child feeding has been noted widely in literature across geographies (Almeida, Scagliusi, Duran, & Jaime, ; Angeles‐Agdeppa, Lana, & Barba, ; Babington & Patel, ; Feeley et al, ; Machín, Giménez, Curutchet, Martínez, and Ares (); Kavle et al, ; Pries, Huffman, Adhikary, et al, ; Pries, Huffman, Mengkheang, et al, ; Rahman et al, ; Verma & Punia, ; Vitta et al, ). Child preference was the most common reason reported by caregivers in this study; however, this response may serve as an initial catch‐all response.…”
Section: Discussionmentioning
confidence: 99%
“…In Bangladesh, Rahman et al () found that mothers perceived packaged snack foods as not safe for children but still reported feeding them because children preferred the taste. Parents often face competing factors when making child feeding decisions, with convenient and flavourful products serving as a reluctant solution (Almeida et al, ; Maubach, Hoek, & McCreanor, ). If interventions aim to discourage caregivers from relying on unhealthy snack food and beverage products, they could consider integrating features of snack food products that appeal to mothers (palatable to children and easy to prepare/ready to eat) into high‐quality, nutritious food options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duran et al 16 proposed an audit instrument designed to audit retail food establishments and restaurants and to measure aspects such as availability, variety, quality, price, and advertising of healthy food indicators such as fruits and vegetables and of unhealthy food indicators such as ultraprocessed foods. The main differences of the AUDITNOVA developed and validated in this study comparing with the other two Brazilian instruments were the full use of the NOVA classification in the food item selection, the expansion of advertising and promotional strategies by food groups, the availability of 66 food items (including culinary ingredients and processed foods), the inclusion of strategic aspects of the consumer food environment (such as checkout aisles, endcaps, and islands), and the collection of information on normal or promotional prices, determining factors in the food acquisition by the population 1,9,14,20 .…”
Section: Mean (Sd) Researcher 1 Mean (Sd) Researcher 2 R Mean (Sd) VImentioning
confidence: 99%
“…Using a socioecological behavior approach, Glanz et al 1 suggest a conceptual model that divides the food environment into four main domains: community food environment, organizational food environment, information food environment, and consumer food environment. The latter refers to what consumers find inside and around retail food establishments, for example, healthy food availability, variety, price, promotions, shelf position, nutritional information, and advertising, determining factors in decision-making processes of food acquisition and consumption by the population 8,9 . For example, a study in the United States found only 7% of the total food information in the weekly circulated leaflet from a supermarket chain was about fruit, 10% about vegetables, 10% about milk and dairy products, and 18% about cereals and grains; moreover, it showed information in these leaflets often influence consumers when making their food purchases 10 .…”
Section: Introductionmentioning
confidence: 99%